Chapter name: “The Effects of Propolis in Animals Exposed Oxidative Stress” (Chapter 13): "Oxidative Stress - Environmental Induction and Dietary Antioxidants" - Tatlı Seven, Pınar; Yılmaz, Seval; Seven, İsmail; Tuna Keleştemur, Gülüzar (My University, 2012)
Oxidative Stress is a general term used to describe the effect of oxidation in which an abnormal level of ROS, such as the free radicals (e.g. hydroxyl, nitric acid, superoxide) or the non-radicals (e.g. hydrogen peroxide (H2O2), lipid peroxide) lead of damage (called oxidative damage) to specific molecules with consequential injury to cells or tissue. Oxidative stress is caused by an imbalance between the production of reactive oxygen and a biological system's ability to readily detoxify the reactive intermediates or easily repair the resulting damage (
Kitap - Çok Yazarlı Kitap
Keywords: Fırat Üniversitesi Kütüphanesi; propolis; animal